Prevalence and risk factors of mcr-1-positive volunteers after colistin banning as animal growth promoter in China: a community-based case–control study. (February 2022) - Lv, Ziquan; Shen, Yingbo; Liu, Weiwen; Ye, Hailing; Liu, Dejun; Liu, Juan; Fu, Yulin; Peng, Changfeng; Chen, Kun; Deng, Xiangxiao; Liu, Bang; He, Jie; et al.
Abstract: Objectives: China banned the use of colistin as animal growth promoter in April 2017. Herein, we report the prevalence of mcr-1 in the intestine of healthy humans and risk factors associated with mcr-1 carriage after the implementation of the ban. Methods: We recruited 719 healthy volunteers from Shenzhen City from 1 March 2018 to 31 December 2019 to investigate the prevalence of mcr-1 in human intestine, and undertook a case–control study to ascertain the risk factors associated with the mcr-1 -positive population. A further comparative study was conducted to identify differences between genetic characteristics of mcr-1 -positive and mcr-1 -negative Escherichia coli . Results: Overall, 56 (7.8%, 95% CI 5.9%–10.0%, n  = 719) individual faecal samples were positive for mcr-1, and prevalence of mcr-1 among individuals in 2019 (2.4%, 95% CI 8.7%–15.0%, 7/294) was significantly lower than that in 2018 (11.5%, 95% CI 1.0%–4.8%, 49/425) (p < 0.0001). After the colistin ban, animal-derived food (pork and chicken meat) was no longer a risk factor for mcr-1 carriage in human intestine, whereas a higher intake of fish and seafood (>75 g/day) and whole grains (>150 g/day) was associated with higher and lower risk of mcr-1 carriage, respectively (OR 2.175, 95% CI 1.047–4.517; OR 0.045, 95% CI 0.004–0.567). Compared with mcr-1 -negative E. coli, the mcr-1 -positive E. coli had different patterns of resistance genes and genetic heterogeneity. Conclusions: Our study implicates aquatic food as beeing associated with mcr-1 carriage in the healthy population, even after the ban on colistin. Dietary modification (e.g. whole grains) may help to combat mcr-1 -positive bacterial colonization of the gut.